Coordinated external-extension toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating and preparation method of coordinated external-extension toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating
By using Zr metal target and TiAlSi composite target in a reactive magnetron sputtering meter, the content ratio of Si:TiAl is controlled, and the modulation layer is transformed into a lattice structure with the same template layer, forming a co-epitaxially grown ZrN/TiAlN-Si3N4 nano-multi-layer structural coating, which solves the impact of heterogeneization on performance and achieves the improvement of strength and toughening and oxidation resistance.
Patent Information
- Application Number
- CN202411733139.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the influence of heterogeneization caused by changes in the Si element content in the modulation layer on various properties of ZrN/TiAlN-Si3N4 nano-multilayer films has been rarely studied, resulting in insufficient hardness and oxidation resistance.
By using Zr metal target and TiAlSi composite target in a reactive magnetron sputtering meter, the content ratio of Si:TiAl is controlled, and the modulation layer is transformed into a lattice structure with the same template layer, thereby forming a coextensively epitaxially grown ZrN/TiAlN-Si3N4 nano-multilayer structure coating.
The nano-multi-layer structural coating is strengthened, the hardness and oxidation resistance are improved, the sliding of nano-grain particles along the grain boundary is suppressed, and the service life of the equipment is extended.
Smart Images

Figure CN119530711A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating and a preparation method thereof, belonging to the technical field of novel hard protective coatings. Background Art
[0002] Nanofilms based on the transition metal (TM) zirconium are widely used in industry as hard protective films for surface hardening of cutting tools, stamping machinery, mold parts, etc., due to their high hardness, good wear resistance, thermal stability, and oxidation resistance. However, the brittleness of nanofilms leads to cracks and delamination defects, which reduces the service life of the equipment.
[0003] The Si element not only has good thermal stability, but also can form a Si3N4 modulation layer phase that is incompatible with the matrix during the film growth process, thereby forming a nanocomposite reinforcement structure. At the same time, due to the encapsulation of the Si3N4 modulation layer phase, it also plays an important role in grain refinement. In order to improve the mechanical properties and oxidation resistance of TiN / Ag films, Ju et al. prepared TiN / Ag / Si3N4 composite films by radio frequency magnetron co-sputtering. When the Si content increased to 15.3at.%, the columnar morphology of the film disappeared. The hardness of the film increased from ~16GPa to ~24GPa. The formation of Si3N4 causes grain refinement and heterogeneous interface strengthening, which helps to improve the hardness. At the same time, the addition of silicon significantly increases the anti-oxidation temperature of the film and effectively prevents the diffusion of Ag. Zhang et al. successfully prepared CrN / Si3N4 multilayer films containing different Si contents by combining deep oscillation magnetron sputtering and pulsed DC magnetron sputtering. Excellent nc-CrN / a-Si3N4 interface formation makes the hardness, H / E, H of the nano-multilayer film 3 / E 2 and K IC Reached 30.6GPa, 0.099, 0.387 and 3.69MPa·m 1 / 2 The coating enhances the cooperative deformation ability through energy dissipation and stress relaxation at the nc-CrN / a-Si3N4 interface, thereby reducing the occurrence and propagation of cracks and adhesion failure, and exhibiting excellent mechanical properties. Li et al. prepared SiN with different x Layer thickness of CrAlN / SiN x Nano-multilayer film. The research results show that when SiN x When the layer thickness is less than 0.6nm, SiN x Forced to crystallize and grow coepitaxially with the CrAlN layer, the average dislocation density is reduced, while the hardness and elastic modulus are enhanced; x As the layer thickness increases, the crystallized SiN xThe layer is transformed into an amorphous state, resulting in an increase in the average dislocation density and a decrease in hardness and elastic modulus. In addition, Li et al. also studied the effect of Si doping on the microstructure and superhardness effect of CrN / TiSiN and TiN / CrAlSiN nano-multilayer films. When Si doping reaches a certain ratio, the modulation layer maintains coherent epitaxial growth under the action of the template layer. x The thermodynamic incompatibility can effectively refine the columnar crystal structure of the nano-multilayer film, resulting in a superhardness effect.
[0004] Doping Si into TiAlN film can form TiAlN-Si3N4 quaternary nanocomposite film. There are two crystal phases in the microstructure of the composite film, namely, Si3N4 crystal phase (or amorphous phase) envelops TiAlN crystal phase, forming a network structure, which makes TiAlN grains maintain the growth state at the nanoscale. However, there are few studies on the effect of multiphase phenomenon caused by the change of Si content in the modulation layer on the various properties of ZrN / TiAlN-Si3N4 nano-multilayer film.
[0005] Therefore, there is an urgent need in the art for a coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano-multilayer structure coating and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to solve the problem in the prior art that there is little research on the influence of the multiphase phenomenon caused by the change of Si element content in the modulation layer on various properties of the ZrN / TiAlN-Si3N4 nano multilayer film.
[0007] In order to achieve the purpose of solving the above problems, the technical solution adopted by the present invention is to provide a coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating and a preparation method thereof.
[0008] The first aspect of the present invention provides a method for preparing a coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating, comprising the following steps:
[0009] Step 1: cleaning the substrate, wherein the substrate is metal, cemented carbide, ceramic or single crystal Si;
[0010] Step 2: Preparation of ZrN / TiAlN-Si3N4 nano multilayer structure coating: Place the substrate into a reactive magnetron sputtering apparatus and place it on the Zr metal target and the TiAlSi composite target respectively, and obtain a coherent epitaxial ZrN / TiAlN-Si3N4 nano multilayer structure coating by reactive magnetron sputtering deposition; the process control of the reactive magnetron sputtering deposition is as follows:
[0011] Zr metal target and TiAlSi composite target are used, with a target diameter of 75mm and a thickness of 3mm;
[0012] DC sputtering power 160W, RF sputtering power 120W;
[0013] The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r;
[0014] Target substrate distance 50mm;
[0015] Total air pressure 0.6Pa.
[0016] Preferably, in the step 1, the method for cleaning the substrate comprises: sending the polished substrate into an ultrasonic cleaning machine, and cleaning it in analytical pure anhydrous alcohol and acetone in turn using 15-30kHz ultrasonic waves for 15 minutes; then performing ion cleaning; the ion cleaning is to place the substrate into a vacuum chamber, evacuate it to 4×10-3Pa, then introduce Ar gas, maintain the vacuum degree at 2-4Pa, and bombard the target material with argon ions for 10 minutes.
[0017] Preferably, in step 2, the content ratio of Si:TiAl is controlled to be 1:24, 2:23, 3:22, 4:21 and 5:20.
[0018] Preferably, in step 2, the thickness of the ZrN / TiAlN-Si3N4 nano multilayer structure coating is 1,296 nm.
[0019] Preferably, in step 2, the ZrN / TiAlN-Si3N4 nano multilayer structure has periodic lattice fringes, the modulation layer is transformed into the same crystal structure as the main layer, and the coating has continuous columnar grains with good crystallinity.
[0020] The second aspect of the present invention provides a coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano-multilayer structure coating prepared by the above method.
[0021] Preferably, in the ZrN / TiAlN-Si3N4 nano multilayer structure coating, the Si:TiAl content ratio is 1:24, 2:23, 3:22, 4:21 and 5:20, and more preferably 4:21.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] A coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano-multilayer structure coating of the present invention, according to the deformation mechanism of the nano-coating, when the grain size is small enough, especially less than 10nm, dislocation movement is no longer a microscopic mechanism of material deformation, and material deformation mainly depends on the slip movement of nano-grains along the grain boundaries. In the preparation of the ZrN / TiAlN-Si3N4 nano-multilayer structure coating of the present invention, by adjusting the content ratio of Si:TiAl in the composite target material, the modulation layer is transformed into a lattice structure having the same lattice structure as the template layer, so that the coating interface forms a coherent epitaxial growth morphology. The slip of nano-grains along the grain boundaries is hindered, thereby suppressing the microscopic deformation of the ZrN / TiAlN-Si3N4 nano-multilayer structure coating, and the nano-multilayer structure coating is further strengthened and toughened.
[0024] In addition, the preparation method of the coherent epitaxially strengthened ZrN / TiAlN-Si3N4 nano multilayer structure coating of the present invention has the advantages of high production efficiency, low energy consumption, and low equipment requirements in the preparation process, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of ZrN / TiAlN-Si3N4 nano-multilayer coatings with different Si:TiAl content ratios;
[0026] Figure 2 HRTEM photos of the cross section of the ZrN / TiAlN-Si3N4 nano-multilayer structure coating: (a) low magnification, (b) medium magnification, (c) high magnification, and (d) selected area electron diffraction pattern;
[0027] Figure 3 The relationship between the hardness and elastic modulus of ZrN / TiAlN-Si3N4 nano multilayer coating and the Si:TiAl content ratio;
[0028] Figure 4 Fracture toughness curves of ZrN / TiAlN-Si3N4 nano-multilayer coatings with different Si:TiAl content ratios. DETAILED DESCRIPTION
[0029] In order to make the present invention more clearly understood, a preferred embodiment is described in detail with reference to the accompanying drawings as follows:
[0030] Preparation, characterization and measurement instruments used in the present invention:
[0031] JGP-450 magnetron sputtering system, Shenyang Scientific Instrument Research and Development Center Co., Ltd., Chinese Academy of Sciences
[0032] D8 Advance X-ray diffractometer, Bruker, Germany
[0033] Bruker TI-980 nanoindenter, Bruker, Germany
[0034] Tecnai G2 20 high-resolution transmission electron microscope, FEI Company, USA
[0035] Quanta FEG450 scanning electron microscope, FEI Company, USA
[0036] Example 1
[0037] The method for preparing the ZrN nanostructured coating is to use a reactive magnetron sputtering apparatus to deposit a Zr metal target on a substrate by reactive magnetron sputtering; the substrate is single crystal Si.
[0038] Use Zr metal target with a diameter of 75mm and a thickness of 3mm;
[0039] Ar gas flow rate: 30 sccm, N2 gas flow rate: 10 sccm;
[0040] DC sputtering power 160W, RF sputtering power 0W;
[0041] The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r;
[0042] The target substrate distance is 50 mm, and the total gas pressure range is 0.6 Pa.
[0043] The hardness of the obtained ZrN nanostructured coating is 13.1 GPa, the elastic modulus is 176.84 GPa, and the fracture toughness is 1.24 MPa·m 1 / 2
[0044] Example 2
[0045] The preparation method of the above-mentioned coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating is to use a reactive magnetron sputtering apparatus to deposit Zr metal target and TiAlSi composite target on a substrate by reactive magnetron sputtering; the substrate is single crystal Si.
[0046] Zr metal target and TiAlSi composite target were used, the Si:TiAl content ratio was set to 1:24, the target diameter was 75 mm, and the thickness was 3 mm;
[0047] Ar gas flow rate: 30 sccm, N2 gas flow rate: 10 sccm;
[0048] DC sputtering power 160W, RF sputtering power 120W;
[0049] The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r;
[0050] The target substrate distance is 50 mm, and the total gas pressure range is 0.6 Pa.
[0051] The hardness of the obtained ZrN / TiAlN-Si3N4 nano multilayer structure coating is 8.27GPa, the elastic modulus is 102.64GPa, and the fracture toughness is 0.37MPa·m 1 / 2 .
[0052] Example 3
[0053] The preparation method of the above-mentioned coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating is to use a reactive magnetron sputtering apparatus to deposit Zr metal target and TiAlSi composite target on a substrate by reactive magnetron sputtering; the substrate is single crystal Si.
[0054] Zr metal target and TiAlSi composite target were used, the Si:TiAl content ratio was set to 2:23, the target diameter was 75 mm, and the thickness was 3 mm;
[0055] Ar gas flow rate: 30 sccm, N2 gas flow rate: 10 sccm;
[0056] DC sputtering power 160W, RF sputtering power 120W;
[0057] The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r;
[0058] The target substrate distance is 50 mm, and the total gas pressure range is 0.6 Pa.
[0059] After testing, the hardness of the obtained ZrN / TiAlN-Si3N4 nano multilayer structure coating is 8.54GPa, the elastic modulus is 131.89.64GPa, and the fracture toughness is 0.52MPa·m 1 / 2 .
[0060] Example 4
[0061] The preparation method of the above-mentioned coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating is to use a reactive magnetron sputtering apparatus to deposit Zr metal target and TiAlSi composite target on a substrate by reactive magnetron sputtering; the substrate is single crystal Si.
[0062] Zr metal target and TiAlSi composite target were used, the Si:TiAl content ratio was set to 3:22, the target diameter was 75 mm, and the thickness was 3 mm;
[0063] Ar gas flow rate: 30 sccm, N2 gas flow rate: 10 sccm;
[0064] DC sputtering power 160W, RF sputtering power 120W;
[0065] The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r;
[0066] The target substrate distance is 50 mm, and the total gas pressure range is 0.6 Pa.
[0067] The hardness of the obtained ZrN / TiAlN-Si3N4 nano multilayer structure coating is 12.39 GPa, the elastic modulus is 180.97 GPa, and the fracture toughness is 0.44 MPa·m 1 / 2 .
[0068] Example 5
[0069] The preparation method of the above-mentioned coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating is to use a reactive magnetron sputtering apparatus to deposit Zr metal target and TiAlSi composite target on a substrate by reactive magnetron sputtering; the substrate is single crystal Si.
[0070] Zr metal target and TiAlSi composite target were used, the Si:TiAl content ratio was set to 4:21, the target diameter was 75 mm, and the thickness was 3 mm;
[0071] Ar gas flow rate: 30 sccm, N2 gas flow rate: 10 sccm;
[0072] DC sputtering power 160W, RF sputtering power 120W;
[0073] The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r;
[0074] The target substrate distance is 50 mm, and the total gas pressure range is 0.6 Pa.
[0075] The hardness of the obtained ZrN / TiAlN-Si3N4 nano multilayer structure coating is 18.46 GPa, the elastic modulus is 226.34 GPa, and the fracture toughness is 0.68 MPa·m 1 / 2 .
[0076] Example 6
[0077] The preparation method of the above-mentioned coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating is to use a reactive magnetron sputtering apparatus to deposit Zr metal target and TiAlSi composite target on a substrate by reactive magnetron sputtering; the substrate is single crystal Si.
[0078] Zr metal target and TiAlSi composite target were used, the Si:TiAl content ratio was set to 5:20, the target diameter was 75 mm, and the thickness was 3 mm;
[0079] Ar gas flow rate: 30 sccm, N2 gas flow rate: 10 sccm;
[0080] DC sputtering power 160W, RF sputtering power 120W;
[0081] The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r;
[0082] The target substrate distance is 50 mm, and the total gas pressure range is 0.6 Pa.
[0083] The hardness of the obtained ZrN / TiAlN-Si3N4 nano multilayer structure coating is 8.38 GPa, the elastic modulus is 125.39 GPa, and the fracture toughness is 0.43 MPa·m 1 / 2 .
[0084] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and equivalent changes made by using the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating, characterized in that: The following steps are involved: Step 1: cleaning the substrate, wherein the substrate is metal, cemented carbide, ceramic or single crystal Si; Step 2: Preparation of ZrN / TiAlN-Si3N4 nano multilayer structure coating: Place the substrate into a reactive magnetron sputtering apparatus and place it on the Zr metal target and the TiAlSi composite target respectively, and obtain a coherent epitaxial ZrN / TiAlN-Si3N4 nano multilayer structure coating by reactive magnetron sputtering deposition; the process control of the reactive magnetron sputtering deposition is as follows: Zr metal target and TiAlSi composite target are used, with a target diameter of 75mm and a thickness of 3mm; DC sputtering power 160W, RF sputtering power 120W; The substrate stays on the two targets for 18s and 8s respectively, and the deposition time is 150r; Target substrate distance 50mm; Total air pressure 0.6Pa.
2. The method for preparing the coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating according to claim 1, characterized in that: In the step 1, the method for cleaning the substrate comprises: sending the polished substrate into an ultrasonic cleaning machine, cleaning it in analytical pure anhydrous alcohol and acetone in turn using 15-30kHz ultrasonic waves for 15 minutes; then performing ion cleaning; the ion cleaning is to place the substrate into a vacuum chamber and evacuate it to 4×10 -3 After 300 Pa, Ar gas was introduced to maintain the vacuum degree at 2-4 Pa, and the target was bombarded with argon ions for 10 min.
3. The method for preparing the coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating according to claim 1, characterized in that: In the step 2, the content ratio of Si:TiAl is controlled to be 1:24, 2:23, 3:22, 4:21 and 5:
20.
4. The method for preparing the coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating according to claim 1, characterized in that: In the step 2, the thickness of the ZrN / TiAlN-Si3N4 nano multilayer structure coating is 1,296 nm.
5. The method for preparing the coherent epitaxial toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating according to claim 1, characterized in that: In the step 2, the ZrN / TiAlN-Si3N4 nano multilayer structure has periodic lattice fringes, the modulation layer is transformed into the same crystal structure as the main layer, and the coating has continuous columnar grains with good crystallinity.
6. A coherent epitaxially toughened ZrN / TiAlN-Si3N4 nano-multilayer structure coating prepared by any one of the methods of claims 1 to 5.
7. The coherent epitaxially strengthened and toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating according to claim 6, characterized in that: In the ZrN / TiAlN-Si3N4 nano multilayer structure coating, the Si:TiAl content ratio is 1:24, 2:23, 3:22, 4:21 and 5:
20.
8. The coherent epitaxially toughened ZrN / TiAlN-Si3N4 nano multilayer structure coating according to claim 7, characterized in that: In the ZrN / TiAlN-Si3N4 nano multilayer structure coating, the Si:TiAl content ratio is 4:21.